Double‐Barrel Stent‐Assisted Coiling of a Basilar Artery Fenestration Aneurysm. Issue 3 (18th May 2012) - Kan, Peter; Abla, Adib A.; Dumont, Travis M.; Snyder, Kenneth V.; Hopkins, L. Nelson; Levy, Elad I.; Siddiqui, Adnan H.
<x xml:space="preserve">Abstract</x> ABSTRACT BACKGROUND AND PURPOSE Basilar artery fenestration aneurysms are rare aneurysms, posing unique challenges for endovascular treatment. We report a case of successful treatment of a wide‐necked basilar artery fenestration aneurysm with a novel double‐barrel stent‐assisted coiling technique. CLINICAL PRESENTATION A 50‐year‐old woman presented with headaches. Evaluation revealed an unruptured 7‐mm broad‐based basilar artery fenestration aneurysm that incorporated both limbs of the basilar fenestration and both distal vertebral arteries. INTERVENTION A 4.5 mm × 22 mm Enterprise stent (Codman Neurovascular, Raynham, MA, USA) was deployed from the right limb of the basilar fenestration into the right distal vertebral artery. Similarly, a 2.5 mm × 20 mm Neuroform EZ stent (Boston Scientific, Natick, MA, USA) was placed from the left limb of the basilar fenestration into the left distal vertebral artery. Following stent deployment, the aneurysm was treated with coil‐embolization through a jailed microcatheter. CONCLUSION In the case presented, a double‐barrel stent configuration enabled dense coil embolization of the aneurysm as well as preservation of both basilar fenestration limbs and both distal vertebral arteries.